(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2004)
The aerocosmic and hydrogeophysical complex methods are effective in investigation of ground water runoff as well as compiling corresponding maps and logs. As an example, Aragats massif territory investigation results have been discussed in this article, which permits to apply these methods in analogue volcanic regions.